Towards a hybrid theory: Derivation of a view concept between Model-based Systems Engineering and Data Analytics - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Maker Systems Engineering Systematic: A Practitioner-Driven Research Agenda - Hermelingmeier, Dominik; Bita, Isaac Mpidi; Menne, Leon; Jobelius, Johannes; Tichonov, Denis; Pfeifer, Stefan; Dumitrescu, Roman (Procedia CIRP)

Success Factors in Product Management and the Role of Data - Fichtler, Timm; Petzke, Lisa Irene; Grigoryan, Khoren; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

The Nexus Model: Towards a metamodel for data-driven system models - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Procedia Computer Science)

Linking Abstract Digital Twin Data to 3D Models: A Configurable Approach for Real-Time Adaptation - Eckertz, Daniel; Sander, Mattes; Masroor, Omar; Dumitrescu, Roman (2025 8th International Conference on Information and Computer Technologies (ICICT))

Advanced Systems Engineering - Auswertung des Gesamtbildes ASE - Aktueller Stand zum Ende von AdWiSE - Dumitrescu, Roman; Albers, Albert; Gausemeier, Jürgen; Riedel, Oliver; Lindow, Kai (Forschungsberichte Pflichtabgabe (BMFTR, BMWE…))

AI-Augmented Model-Based Systems Engineering - Bernijazov, Ruslan; Dumitrescu, Roman; Hanke, Fabian; von Heißen, Oliver; Kaiser, Lydia; Tissen, Denis (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract The increasing complexity of modern technical systems necessitates innovative approaches such as Model-Based Systems Engineering (MBSE). In this context, using Artificial Intelligence (AI) emerges as a key enabler for practical application and efficiency improvement. This article introduces a maturity model for AI-based assistance systems in MBSE. It helps companies assess their current automation level in MBSE activities, providing a foundation for strategic planning of process improvements.

Advanced Analytics in Smart Factories: Towards an actionable Taxonomy for Prescriptive Analytics Use Cases - Weller, Julian; Nalavade, Sumit; Gmelch, Oliver; Migenda, Nico; Heuwinkel, Tim; Dumitrescu, Roman (Procedia CIRP)

Evaluation Of The Challenges In Implementing AI Across The Different Phases - Empirical Insights Derived From AI Implementation Projects In Industry - Dondorf, Verena; Happe, Leonie; Hobscheidt, Daniela; Kürpick, Christian; Dumitrescu, Roman (Proceedings of the Conference on Production Systems and Logistics : CPSL 2025)

Generating An Automated Assembly Graph On The Basis Of The 3D-Geometry Of A Product Assembly Group - Disselkamp, Jan-Philipp; Lick, Jonas; Azem, Ghayth; Grothe, Robin; Ptock, Lukas; Meyer, Matthias; Kürpick, Dominik; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Conference on Production Systems and Logistics: CPSL 2025)

Case Study For Introducing Digital Cardboard Engineering - Disselkamp, Jan-Philipp; Lick, Jonas; Ptock, Lukas; Zacke, Julian; Wilk, Marcel; Ostendorf, Jona; Meyer, Matthias; Westphal, Svenja; Kürpick, Dominik; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Conference on Production Systems and Logistics : CPSL 2025)

Is explaining more like showing or more like building? Agency in metaphors of explaining - Porwol, Philip Fabian; Scharlau, Ingrid (Frontiers in Psychology)
Explanations play a crucial role in knowledge transfer and meaning-making and are often described as a co-constructive process in which multiple agents collaboratively shape understanding. However, the metaphors used to conceptualize explaining may influence how this process is framed. This study investigates the extent to which the co-constructive nature of explaining is represented in explaining metaphors. Using a systematic analysis of agency, we examined how these metaphors depict the explanation process and the roles of the agents involved. We found that explaining metaphors lack collaboration between explainer and addressee, constructiveness of the process, as well as bidirectionality and iterativeness. In light of current research on metaphorical framing, the study thus highlights the risk that such explaining metaphors may reinforce a non-co-constructive perspective on explaining and a top-down approach in the development of AI systems as well as other areas.

Integration eines Lehrmoduls zur Demokratiebildung in bildungswissenschaftlichen Seminaren der Universität Paderborn - Wehde, Janis (Demokratiebildung als Querschnittsaufgabe der Lehrer:innenbildung)

A Structured Tool Landscape for Data-Driven ProductManagernent - Grigoryan, Khoren; Bauer, Eliana; Fichtler, Timm; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (2025 IEEE International Conference on Engineering, Technology, and Innovation (ICE/ITMC))

Testing, modelling and parameter identification for adhesively bonded joints under the combined influence of temperature and strain rate - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik (Journal of Adhesion Science and Technology)

The more-than-human biopolitics of swarming – complexity, emergence, and control in military robotics - Hälterlein, Jens (European Journal of International Security)

Fairness - Hambach, Dennis; Settnieri, Julia (Leistungsmessung, Evaluation und Feedback im Fremdsprachenunterricht - Ein Handbuch für Studium, Refendariat und Unterricht)

Prudence and prevention – empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik (Economics Letters)

Design Space Exploration for Approximate Circuits via Checkpointing and DNN-Based Estimators - Awais, Muhammad; Mohammadi, Hassan Ghasemzadeh; Platzner, Marco (IEEE Transactions on Very Large Scale Integration (VLSI) Systems)

A Two-Stage Approximation Methodology for Efficient DNN Hardware Implementation - Hadipour, Amir Hossein; Jafari, Atousa; Awais, Muhammad; Platzner, Marco (2025 IEEE 28th International Symposium on Design and Diagnostics of Electronic Circuits and Systems (DDECS))